Serotype diversity of Streptococcus mutans and caries activity in children in Argentina - Carletto Körber, F. P. M. (2015)
Aim: The purpose of this study was to analyze the serotype distribution of S. mutans and their association with caries activity in scholar children from Córdoba, Argentina. Material and methods: Clinical examination was performed in 133 children. The dmft+DMFT and Significant Caries (SiC) indices were calculated to identify individuals with high caries activity. After DNA extractions of S. mutans strains, serotypes were determined by PCR amplifications. The median caries activity of each serotype group was compared using a non-parametric Kruskall-Wallis test. Results and Statistics: We obtained S. mutans strains from stimulated saliva of 94 children. The mean dmft+DMFT was 4.14 and the mean SiC group was 8.65. Serotype c was the most frequent (53.2%), followed by e (31.9%), f (8.5%) and k (6.4%). The comparison between the SiC and Non-Sic groups showed significant differences in the frequency of serotypes c and k. The median caries activity was non-significant in the different serotypes. Conclusion: The difference between the serotype frequencies detected in Argentina compared to those of other countries could be related with contrasting dietary habits. The results obtained in the present study would increase the knowledge about the epidemiology of dental caries in children from Argentina.